LEADERSHIP ABOVE THE CLOUDS: A SYSTEMATIC LITERATURE REVIEW OF THE PERSONALITY TRAITS APPROACH LEADERSHIP IN AVIATION - Putriekapuja, Rany Adiliawijaya; Umi Hanifah, Mutiara Ayu (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
With the widespread integration of information technology across industries, including aviation, leadership development now emphasizes technical expertise and soft skills. This study explores the relationship between leadership and airworthiness in aviation, focusing on organizational processes and culture that uphold aviation safety and aircraft airworthiness. The methodology in this research using systematic literature review (SLR) followed PRISMA 2020 guidelines. A systematic literature review (SLR) analyzes how personality traits influence leadership behaviors and effectiveness in aviation and examines the role of personality trait approaches in leadership skills development. Findings highlight the complex interplay of personality traits in determining leadership effectiveness, which is crucial for fostering a culture of safety and airworthiness in aviation operations. This study underscores the importance of personality trait approaches in cultivating competent leaders capable of navigating the complexities of the aviation industry.